Alcohol and Alcohol Effects: Constituting Causality in Alcohol Epidemiology. (September 2014) - Hart, Aaron; Moore, David
Taking cues from Science and Technology Studies, we examine how one type of alcohol epidemiology constitutes the causality of alcohol health effects, and how three realities are made along the way: (1) alcohol is a stable agent that acts consistently to produce quantifiable effects; (2) these effects may be amplified or diminished by social or other factors but not mediated in other ways; and (3) alcohol effects observable at the population level are priorities for public health. We describe how these propositions are predicated upon several simplifications and that these simplifications have political implications, including the attribution of responsibility for health effects to a pharmacological substance; the deletion of other agentic forces that might share responsibility; and a prioritization of simple effects over complex effects. We argue that epidemiological research on alcohol might expand its range of ontological, epistemological and methodological practices to identify new ways of understanding and addressing health effects.